Inclusive Development In AfrIca : Transformation of Global Relations - Gumede, Vusi (Project Muse, 2018)
This book addresses a fundamental developmental challenge for Africa: given all that we know about pertinent issues, what should be done to ensure effective development in Africa? The changing imperatives of international development, the reform of international finance institutions and the growth-development nexus debates as well as varied implications for Africa emanating from global economic crises are critical if Africa's development is to be better understood. Undoubtedly, revisiting the origins, contexts, complexities and contradictions of the lopsided global order and their effects on development and implications for Africa's development is necessary. Contributions emphasise the need to radically transform global relations and to accelerate the pursuit of our quest for inclusive development in Africa; acknowledging that we must further problematise Africa's development in the context of the obtaining global power dynamics and systematically examine the implications of the global economic crises for women as well as for land and agrarian reforms. The book is a timely contribution to our understanding of the global realities confronting Africa, with specific suggestions on how to improve development.